Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1103/physrevlett.109.076603
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Performance of Organic Spintronic Devices Using X-Ray Generated Traps

Abstract: X rays produced during electron-beam deposition of metallic electrodes drastically change the performance of organic spintronic devices. The x rays generate traps with an activation energy of ≈0.5  eV in a commonly used organic. These traps lead to a dramatic decrease in spin-diffusion length in organic spin valves. In organic magnetoresistive (OMAR) devices, however, the traps strongly enhance magnetoresistance. OMAR is an intrinsic magnetotransport phenomenon and does not rely on spin injection. We discuss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 36 publications
4
68
1
Order By: Relevance
“…1a, where the band does not have a local minimum to keep extra charges inside the organic once a bias is removed. While impurities or deep traps have been shown to influence the MR in the OSVs 23 , the present model suggests that the impurity band due to high-density impurities is responsible for charge/spin transport in the OSVs.…”
Section: Forward Biasmentioning
confidence: 63%
“…1a, where the band does not have a local minimum to keep extra charges inside the organic once a bias is removed. While impurities or deep traps have been shown to influence the MR in the OSVs 23 , the present model suggests that the impurity band due to high-density impurities is responsible for charge/spin transport in the OSVs.…”
Section: Forward Biasmentioning
confidence: 63%
“…Interestingly, a first step on this road was recently taken in Alq 3 devices by exposing them to x rays, leading to an enhancement of the MC. 47 Whether this same process could be applied to other devices is debatable as the exact nature of traps is still under investigation. Recently, an elaborate study suggested that hydrated oxygen complexes can explain the electron traps in most semiconducting polymers.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time the shadow mask protects the OSC in the active area inside the AlOx window from any damage by the electron beam evaporation by high energy electrons or X-ray Bremsstrahlung. 19 Finally the sample is bonded for measurements in the cryostat.…”
Section: Nanosized Vertical Organic Spin-valvesmentioning
confidence: 99%